Teaching learning in the supervised curricular training in an IF: possibilities and weaknesses (Research, Society and Development, 2022)
His study aims to identify the possibilities and weaknesses of the Supervised Curricular Internship process of the Degree in Chemistry of a Federal Institute of Education, Science and Technology, in Rio Verde, called IF Campus, for teaching learning. As a methodological procedure, we use documents and narrative collection from eight trainees of the undergraduate degree in Chemistry. The questions that led the research were: Does IF Campus Supervised Curricular Internship contribute to teaching learning? How do these contributions occur? What are the limits and weaknesses of this process? The results indicate that the Supervised Curricular Internship has contributed significantly to the learning of the teaching of the interns by enabling their approach with the school environment and the development of activities that enable initiation to research. However, weaknesses we found, such as lack of articulation between the Supervised Curricular Internship and the other disciplines of the course and the absence of an effective use of theoretical references to support the development of activities and reflections of Supervised Curricular Internship.